Adequate Compensation Valuation by Public Valuer and Private Valuer in Malacca - Phan Jia-Jian; mohsen, masfaliza; Zarina Shamsudin; Indera Syahrul Mat Radzuan (Research in Management of Technology and Business, 2021)
An insufficient compensation in a land acquisition will cause the landowner appeal to Court to claim for their intended amount of compensation. However, the community may not have sufficient of knowledge to know the rights regarding to land acquisition matters. To ensure that nobody is violated or suspects the acquisition of land is done by coercion, it will be pursuant to law and legal procedures. Article 13 of the Federal Constitution states that no person shall be deprived of his property except under law and no law may make provision for the taking or use or use of the property by force unless sufficient compensation. Any land acquisition should therefore be paid with sufficient compensation. Therefore, the factors of consideration that determine the adequacy of compensation by public and private valuers during the acquisition process are very essential to know and understand. Secondly, to determine the composition of objection in Land Acquisition Act 1960, under Section 37, Form N apply by the landowner to the Court. This study conducted qualitativelyAn insufficient compensation in a land acquisition will cause the landowner appeal to Court to claim for their intended amount of compensation. However, the community may not have sufficient of knowledge to know the rights regarding to land acquisition matters. To ensure that nobody is violated or suspects the acquisition of land is done by coercion, it will be pursuant to law and legal procedures. Article 13 of the Federal Constitution states that no person shall be deprived of his property except under law and no law may make provision for the taking or use or use of the property by force unless sufficient compensation. Any land acquisition should therefore be paid with sufficient compensation. Therefore, the factors of consideration that determine the adequacy of compensation by public and private valuers during the acquisition process are very essential to know and understand. Secondly, to determine the composition of objection in Land Acquisition Act 1960, under Section 37, Form N apply by the landowner to the Court. This study conducted qualitatively by collecting actual case studies. The valuation report by public and private valuer and the amount of award by Land Administrator will be collected and analyzed to achieve the objectives. The findings of this study will outline different factors of consideration in determining a compensation due to various parties involved in the valuation. The composition of objection which clearly outlined the ground of appeal will also be identified. The scope of the study was in Malacca.by collecting actual case studies. The valuation report by public and private valuer and the amount of award by Land Administrator will be collected and analyzed to achieve the objectives. The findings of this study will outline different factors of consideration in determining a compensation due to various parties involved in the valuation. The composition of objection which clearly outlined the ground of appeal will also be identified. The scope of the study was in Malacca.